Customer Segment Research and its Role in Designing Sales Promotion Programme for Small Car Industry in India - Misra, Madhvendra (Indian Journal of Marketing, 2007)
The paper tries to associate the significance of information generated by the customer segment research to the help, which it can extend in designing the sales promotion programme and related tools and strategy. The fundamentals of the paper are based on the customer survey conducted over 434 potential buyers of small car, identified in the population on basis of probability sampling. In the analytical approach to utilise the information thus generated through the customer research, few assumptions are taken into account with reference to family life cycle and related aspects. Further on in the paper the features are mapped to the preference sets of the customer segment zeroing to 'highest potential buyer group' in the targeted population. The resultant is associated with types of sales promotion tools and strategy that can induce a favourable purchase decision. The paper utilises Set Theory to an extent to determine overlapping and converging areas of interest in the customer preference set.